Electrophysical properties of A3 IILaNb3O12 (AII = Sr, Ba) with slab perovskite-like structure - Titov, Y.A.; Slobodyanik, M.S.; Kuzmin, R.N.; Chumak, V.V. (Reports of the National Academy of Sciences of Ukraine, 2021)
High-stoichiometric polycrystalline samples of cation-deficient niobates A3IILaNb3O12(AII = Sr, Ba) with a three-slab perovskite-like structure were synthesized by the heat treatment of a charge of co-precipitated hydroxycarbonates. The electrophysical properties of ceramic samples made from them are investigated by the method of impedance spectroscopy. To simulate the impedance spectrum, the method of equivalent circuits represented by radio engineering elements was used. It allows one to isolate, in pure form, the properties of microcrystalline grains of a ceramics, that is, the substance under study itself, without the influence of the intercrystalline and electrode effects. The dependences of the complex impedance Z (v) of these compounds on the frequency (0.1-106 Hz) of the probing sinusoidal electrical signal and temperature (300-700 K) have been established and analyzed. The temperature dependence of the d. c. electrical conductivity, temperature and frequency dependences of the real component of the dielectric constant ε'‎, as well as the activation energies of the electrical conductivity of A3IILaNb3O12 ceramic grains (AII = Sr, Ba) were determined. The possibility of using the synthesized materials for the manufacture of thermistors highly sensitive and resistant to aggressive operating conditions with a nonlinear characteristic and a wide range of operating temperature has been established.